2019
DOI: 10.1016/j.brs.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation in refractory and super-refractory status epilepticus – A systematic review

Abstract: Rationale: Refractory status epilepticus (RSE) is the persistence of status epilepticus despite second-line treatment. Super-refractory SE (SRSE) is characterized by ongoing status despite 48 h of anaesthetic treatment. Due to the high case fatality in RSE of 16e39%, off label treatments without strong evidence of efficacy in RSE are often administered. In single case-reports and small case series totalling 28 patients, acute implantation of VNS in RSE was associated with 76% and 26% success rate in generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 62 publications
2
59
0
9
Order By: Relevance
“…About 50% to 60% of patients achieve 50% reduction in seizure frequency after 1 year of treatment (Englot et al, 2016;Kawai et al, 2017;Panebianco et al, 2015). A recent meta-analysis (Dibué-Adjei et al, 2019) suggested that acute VNS implantation could reverse refractory status epilepticus, with an overall response rate of 74%. However, mechanisms underlying the effects of VNS remain misunderstood (Vonck and Boon, 2015).…”
mentioning
confidence: 99%
“…About 50% to 60% of patients achieve 50% reduction in seizure frequency after 1 year of treatment (Englot et al, 2016;Kawai et al, 2017;Panebianco et al, 2015). A recent meta-analysis (Dibué-Adjei et al, 2019) suggested that acute VNS implantation could reverse refractory status epilepticus, with an overall response rate of 74%. However, mechanisms underlying the effects of VNS remain misunderstood (Vonck and Boon, 2015).…”
mentioning
confidence: 99%
“…Vagus nerve stimulation is widely used as a seizure-preventive action in many types of otherwise incurable epilepsy and is extensively studied for treating other conditions ranging from rheumatoid arthritis to depression (Vonck et al, 2001;Groves and Brown, 2005;Yuan and Silberstein, 2016;Dibue-Adjei et al, 2019;Noller et al, 2019). It is well-known that vagus nerve is engaged in the bidirectional information transfer between the internal organs and the brain, but how changes in activity going along visceral pathways may be related to paroxysmal events occurring in various brain areas remained unclear.…”
mentioning
confidence: 99%
“…De Benedictis et.al report a series of four patients with SE who saw an improvement in seizure after 5 weeks since stimulation onset, and a persistence of the effect after a mean follow-up of 3 years [ 82 ]. On the other hand, a review of 17 papers did not recommend the use of VNS for resistant status epilepticus (RSE); nevertheless, a more recent review by Dibué-Adjei concludes that VNS can interrupt RSE in 74% of patients, with a class IV evidence level [ 83 ]. VNS was considered as a promising tool in the prevention or reduction in sudden unexpected death in epilepsy (SUDEP) [ 84 , 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%